(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Among the non-verbal actions that are not expressed in words, smiling and laughing have a special place, and this is a very important xenic position: there are gestures, facial expressions, gestures and expressive facial signs in international culture. Learning and knowing how to smile and not smile in interpersonal diplomatic relations is considered to be a strategy of keeping the interlocutor close to oneself. Neuropsycholinguistics helps to study subtle aspects of smile. This is one of the practically unsolved problems of neuropsicholinguistics. The brain is a mysterious world, if it is studied from the point of view of the influence of speech, how we perceive language, how we talk becomes easier. Laughter and smiling also calm the human brain. They also nourish the human psyche and renew his spiritual world. A laughter and a smile smile are a very delicate matter, it is necessary to know its place and learn ways to give it to someone.